Development of a multimedia courseware for slow learner children with reading difficulties: MyLINUS - Wan Ahmad, W.F. (2013)
This paper presents the development of a multimedia courseware namely 'My LINUS' as a medium in teaching and learning specially designed for slow learner with reading difficulties. The courseware will help slow learner children using an approach and a suitable technique/method with appropriate teaching materials essential for the learning process. The courseware integrates Literacy and Numeracy (LINUS) Syllabus officially prepared by the Ministry of Education for primary school children aged between 7 to 9 years old with the learning multimedia theme. The "MyLINUS" primarily consists of 2 sections for the modules and exercises. The modules consist of 3 sub-modules. Each module is designed to teach in certain domain starting from Module 1 till Module 3. Module 1 teaches the users on how to recognize and pronounce a letter. Module 2 teaches users on how to combine letters to form a word. Module 3 guides users on how to combine words and syllable to form complete sentences. A user acceptance test was conducted in two primary schools in Perak. The results help to support suitability and acceptability and the effectiveness of the courseware for further improvement. The findings of the evaluation indicate positive feedback about the courseware. Â© 2013 Springer International Publishing.